Effects of plastic sheet on water saving and yield under furrow irrigation method in semi-arid region - Memon, Muhammad Sohail; Ali, Kausar; Siyal, Altaf Ali; Guo, Jun; Memon, Shamim Ara; Soomro, Shakeel Ahmed; Memon, Noreena; Ji, Changying (International Journal of Agricultural and Biological Engineering, 2018)
The increasing demand of water in the country highlights the need to introduce low-input and water saving technologies for agricultural sustainability and crop production, mainly in semi-arid region. A study was conducted to minimize deep percolation losses from the furrow bottom under two different irrigation treatments viz. (1) furrow bottom with plastic sheet (T1) and (2) furrow bottom without plastic Sheet (T0). The physical and chemical analyses of soil profile were taken at a depth of 0-80 cm before and after crop harvesting. The dry density of soil slightly increased (0.01 g/cm3) under both treatments, while soil pH decreased under T1. The average yield was 8332 kg/hm2 and 7575 kg/hm2, with 21.56 m3 and 31.09 m3 total volume of irrigation water applied under T1and T0, respectively. The saving percentages of water under treatments were 52.22% and 31.00% under T1 and T0 respectively as compared to the saving of water under traditional irrigation practice. Overall, better performance, in terms of crop production and water saving, was obtained with use of plastic sheet integrated with bottom of furrows. Hence, it is suggested that the furrow irrigation method with plastic sheet may be used to preventing moisture and minimize deep percolation losses from furrow bottom.Keywords: furrow irrigation, semi-arid region, water saving, yield, plastic sheet, deep percolation, okra crop, soil pHDOI: 10.25165/j.ijabe.20181101.3186Citation: Memon M S, Ali K, Siyal A A, Guo J, Memon S A, Soomro S A, et al. Effects of plastic sheet on water saving and yield under furrow irrigation method in semi-arid region. Int J Agric & Biol Eng, 2018; 11(1): 172–177.